Archean (3.33 Ga) microbe-sediment systems were diverse and flourished in a hydrothermal context - Westall, Frances (2015)
Interacting, diverse microbe-sediment systems exist in natural environments today but have not yet been recognized in the oldest records of life on Earth (older than 3.3 Ga) because of lack of distinctive biomarker molecules and patchy preservation of microbial paleocommunities. In an in-situ outcrop- to microbial-scale study, we have differentiated probable phototrophic, chemolithotrophic, and chemo-organotrophic fossil microbial signatures in a nearshore volcanogenic sedimentary setting in 3.33 Ga rocks of the Josefsdal Chert, Barberton greenstone belt, South Africa, while demonstrating the importance of contemporaneous hydrothermal activity. Hydrothermal fluids, as a nutrient source, strongly controlled the development and distribution of the microbial communities and, as a silicifying agent, contributed to their rapid fossilization. We thus show that intricate microbe-sediment systems are deep-rooted in time and that at least some early life may indeed have been thermophilic.